2019
DOI: 10.1186/s12862-019-1354-y
|View full text |Cite
|
Sign up to set email alerts
|

Islands and hybrid zones: combining the knowledge from “Natural Laboratories” to explain phylogeographic patterns of the European brown hare

Abstract: BackgroundThe aim of the study was to use hybrid populations as well as island populations of the European brown hare (Lepus europaeus) to explore the effect of evolutionary events, such as the post-deglaciation translocations, spontaneous and human-mediated, local adaptation and the genetic drift in the shaping of the phylogeographic patterns of the species. For this purpose, we used molecular markers, both nuclear and mitochondrial, that are indicative for local adaptation as well as neutral markers to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…In principle, two major evolutionary processes may have shaped the distributional pattern of haplotypes across the study area: firstly, purely neutral evolutionary processes, such as gene flow and regional random drift due to various potential (unknown) population dynamic changes in the evolutionary history, in accordance with the earlier observed distribution of D-loop haplotypes; and secondly, negative or/and positive selection, potentially having only regionally led to deviations from the distributional pattern as expected from neutral evolution. Following Ben Slimen et al [67] and Melo-Ferreira et al [10] that have demonstrated positive selection in mtDNA of various species of hares and jackrabbits (genus Lepus ) and accounting for the fact that isolation of populations in distinct (Pleistocene) refugia may have led to adaptations and differentiation in allopatry [37], we hypothesize that molecular diversity at the particularly highly variable MT-ND6 locus has been shaped by positive selection and adaptation to varying environments in the course of its phylogenetic history. Specifically, positive selection may have led to adaptation in populations from Europe, where more pronounced climatic oscillations have occurred during the Late Pleistocene, with massive ice cover shifts and concomitant extreme changes of vegetation on north-south and east west gradients [38].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, two major evolutionary processes may have shaped the distributional pattern of haplotypes across the study area: firstly, purely neutral evolutionary processes, such as gene flow and regional random drift due to various potential (unknown) population dynamic changes in the evolutionary history, in accordance with the earlier observed distribution of D-loop haplotypes; and secondly, negative or/and positive selection, potentially having only regionally led to deviations from the distributional pattern as expected from neutral evolution. Following Ben Slimen et al [67] and Melo-Ferreira et al [10] that have demonstrated positive selection in mtDNA of various species of hares and jackrabbits (genus Lepus ) and accounting for the fact that isolation of populations in distinct (Pleistocene) refugia may have led to adaptations and differentiation in allopatry [37], we hypothesize that molecular diversity at the particularly highly variable MT-ND6 locus has been shaped by positive selection and adaptation to varying environments in the course of its phylogenetic history. Specifically, positive selection may have led to adaptation in populations from Europe, where more pronounced climatic oscillations have occurred during the Late Pleistocene, with massive ice cover shifts and concomitant extreme changes of vegetation on north-south and east west gradients [38].…”
Section: Introductionmentioning
confidence: 99%
“…Climate factors and habitat environment will profoundly impact the evolution of biological populations, thus leaving historical traces in the genetic diversity, population structure, distribution pattern, and other aspects of today's populations. For example, climate changes profoundly affected phylogeographic structure and the evolutionary history of brown hares (L. europaeus) by isolating populations in the distinct refugia where they adapted and differentiated in allopatry, leading to genome incompatibilities (Djan et al, 2017;Minoudi et al, 2018;Giannoulis et al, 2019). The southwest of Tarim Basin in Xinjiang, China, as the origin of rivers in the basin, was a glacial refugia for Yarkand hares (L. yarkandensis) during the Quaternary climate oscillations, providing a suitable environment for maintaining the relatively high genetic diversity of this species (Shan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The term ’hybrid zones’ refers to the geographical territories where closely related organisms meet and are hybridized [ 127 , 128 ]. They are commonly referred to as natural laboratories for evolutionary biology, because they offer the opportunity for researchers to investigate the evolutionary forces and mechanisms that lead to population disparities [ 128 , 129 ]. Moreover, natural hybrid zones provide more information about the MC phenomenon and its contribution to the hybrid breakdown, since they allow scientists to examine hybrids for many generations and over a long time period, whereas laboratory crosses include a small number of recombination generations [ 130 ].…”
Section: MC Can Lead To the Reproductive Isolation Between Population...mentioning
confidence: 99%
“…The maintenance of the hybrid zones is attributed to two key processes: random dispersal and the selection against hybrids [ 127 ]. However, an interesting fact is that many studies indicate such a large intraspecific variation for many organisms, that boundaries and clear distribution patterns are created in the hybrid zones as the intraspecific populations are not geographically mixed, potentially due to hybrid breakdown [ 127 , 129 ]. These intraspecific phylogeographic patterns and hybrid zones have been well characterized for a variety of organisms in Europe.…”
Section: MC Can Lead To the Reproductive Isolation Between Population...mentioning
confidence: 99%